Hydrodynamic forces and moments on underwater vehicles: A numerical investigation using Flow and Body Rotation at various angles of attack - Krishna, H. Rahul; Issac, M. T.; Ebenezer, D. D. (Journal of Naval Architecture and Marine Engineering, 2026)
Accurate numerical simulation of flow over bodies, when there is an angle of attack, is challenging even when the body is slender and axisymmetric. Two methods are widely used in such simulations, but no study clearly compares the accuracies and the advantages and disadvantages of the methods. In the body rotation method (BRM), the flow is along the axis of the domain, and the body is rotated such that the angle between the main axis of the body and the flow direction is the angle of attack. In the flow rotation method (FRM), the axis of the body is along the axis of the domain, and the direction of the flow is changed to simulate the angle of attack. In the present study, both methods are used at a Reynolds number of . The Computational Fluid Dynamics (CFD) package is used to simulate flow over an axisymmetric three-dimensional (3D) bare hull submarine model, and the angle of attack is varied from 0 to 18. In both BRM and FRM approaches, steady Reynolds Average Navier Stokes (RANS) equations are solved using the Shear Stress Transport (SST) turbulence model, with non-dimensional wall adjacent cell thickness () kept below 1. The same domain and mesh commands are used in both methods. The hydrodynamic forces, moments, coefficients of wall shear stress, and pressure computed using the two methods differ by less than two percent. The distribution of the sizes of cells and the number of cells of various shapes are also presented. When meshed with cells in the wall-adjacent region having the same size, the number of cells and computation time are much less in the body rotation method, and it is therefore preferred. Journal of Naval Architecture and Marine Engineering, 23(1), 2026, PP. 21-40